Percutaneous closure of patent ductus arteriosus via internal jugular vein in patient with interrupted inferior vena cava - Patel Nehal; Madan Tarun; Panchal Amar; Thakkar Bhavesh (Wolters Kluwer Medknow Publications, 2009)
Transcatheter closure of patent ductus arteriosus (PDA) using various occluders and coils via femoral vein is a well established therapeutic option. However, in patients with interrupted inferior vena cava (IVC) it is not feasible to close the PDA percutaneously using traditional methods. We present a nine-year-old girl with IVC interruption in whom percutaneous closure of PDA was successfully accomplished via the transjugular approach.